Propionic Acid Rescues High-Fat Diet Enhanced Immunopathology in Autoimmunity via Effects on Th17 Responses - Haase, Stefanie; Mäurer, Jonas; Duscha, Alexander; Lee, De-Hyung; Balogh, Andras; Gold, Ralf; Müller, Dominik N.; Haghikia, Aiden; Linker, Ralf A. (Frontiers in Immunology, 2021)
High-fat diets (HFD) are linked to obesity and associated comorbidities and induce pathogenic T helper (Th) 17 cells while decreasing regulatory T cells (Treg). This pro-inflammatory environment also aggravates immunopathology in experimental autoimmune encephalomyelitis (EAE) as a prototype model of T cell mediated autoimmunity. The strong association of HFD to obesity as well as the increasing risk of autoimmunity in the Western world stresses the importance to identify compounds that counteract this metabolically induced pro-inflammatory state in humans. One prominent candidate is the short-chain fatty acid propionate (PA) that was recently identified as potent therapy in the autoimmune disease multiple sclerosis by enhancing Treg cell frequencies and functionality. Mice were fed a HFD rich lauric acid (LA) and treated either with water or PA during EAE. We analyzed Treg and Th17 cell frequencies in different tissues, antigen-specific cell proliferation and cytokine secretion, investigated Treg cell functionality by suppression assays and IL-10 signaling blockade and employed Western blotting to investigate the involvement of p38-MAPK signaling. Finally, we performed an explorative study in obese and non-obese MS patients, investigating fecal PA concentrations as well as peripheral Th17 and Treg frequencies before and after 90 days of daily PA intake. As compared to controls, mice on a HFD displayed a more severe course of EAE with enhanced demyelination and immune cell infiltration in the spinal cord. PA treatment prevented this disease enhancing effect by inhibiting Th17 mediated inflammatory processes in the gut and spleen. Blocking experiments and signaling studies revealed p38-MAPK and IL-10 signaling as important targets linking the beneficial effects of PA treatment and reduced inflammation due to enhanced Treg frequency and functionality. An explorative study in a small group of MS patients revealed reduced fecal PA concentrations in obese MS patients compared to the non-obese group, coinciding with increased Th17 but decreased Treg cells. Importantly, PA intake could restore the Treg-Th17 homeostasis. Our data thus identify Th17 responses as an important target for the beneficial effects of PA in HFD and obesity in addition to the recently identified potential of PA as a Treg inducing therapy in T cell mediated autoimmunity.